MENGEMBANGKAN KECERDASAN LINGUISTIK ANAK USIA DINI MELALUI METODE BERNYANYI - Erni Sumarni; Ifat Fatimah Zahro (IKIP Siliwangi, 2022)
The intelligence that must exist in children is linguistic, linguistic intelligence is a person's ability to process or express words, writing, expressing thoughts, desires, and opinions. The purpose of this research is to develop linguistic intelligence in early childhood through the singing method. The method in this research is descriptive and qualitative. Data collection techniques in this study are observation, documentation, and interviews. The subjects in this study were children aged 4-5 years as many as 6 children and 2 teachers, school principals, and parents as informants. The instruments or methods of data collection in this study were observation, interviews, and relevant documentation. Data processing was carried out using qualitative data analysis, namely data reduction, data presentation, conclusion drawing, and verification according to the flow model. The use of qualitative descriptive research in this study is intended for the assessment technique obtained by collecting the results of observations, assessment results, and evaluations of children through developing linguistic intelligence for early childhood through the singing method. The results obtained that the level of children's linguistic achievement through the singing method developed very well and increased, from 6 children studied 5 children developed very well (BSB) in the four indicators studied while 1 child in the last indicator showed development as expected (BSH), this is has proven that there is a positive response from children in the implementation of the singing method.Kecerdasan yang harus ada pada anak adalah kecerdasan linguistik, kecerdasan linguistik adalah kemampuan seseorang untuk mengolah atau mengekspresikan kata-kata, tulisan, ungkapan pikiran keinginan dan pendapat. Tujuan dalam penelitian ini untuk mengembangkan kecerdasan linguistikanak usia dini melalui metode bernyanyi. Metode dalam penelitian ini adalah deskriptif kualitatif. Teknik pengumpulan data dalam penelitian ini yaitu observasi, dokumentasi dan wawancara. Subjek dalam penelitian ini anak usia 4-5 tahun sebanyak 6 anak dan 2 orang guru, kepala Sekolah serta orang tua sebagai informan. Instrumen atau metode pengumpulan data dalam penelitian ini adalah observasi, wawancara dan dokumentasi yang relevan. Pengolahan data yang dilakukan menggunakan analisis data kualitatif yaitu reduksi data, penyajian data, penarikan kesimpulan dan verifikasi sesuai model alir .Penggunaan penelitian deskriptif kualitatif dalam penelitian ini dimaksudkan untuk Teknik penilaian didapatkan dengan mengumpulkan hasil observasi, hasil penilaian dan evaluasi terhadap anak melalui mengembangkan kecerdasan linguistikanak usia dini melalui metode bernyanyi. Diperoleh hasil tingkat pencapaian linguistikanak melalui metode bernyanyi tersebut berkembang sangat baik dan meningkat, dari 6 anak yang diteliti 5 anak berkembang sangat baik (BSB) dalam empat indikator yang diteliti sedangkan 1 anak dalam indikator terakhir menunjukkan berkembang sesuai harapan (BSH), hal ini sudah membuktikan adanya respon positif dari anak dalam pelaksanaan metode bernyanyi tersebut.